Debt and growth: an empirical study of the real effects of debt in the Euro area - Costa, Gonçalo Filipe Pessa Figuereido (2016)
This research investigates the impact of indebtedness on per-capita GDP growth in 12 euro area countries, over a period from 1995 to 2014. Among other contributions, this research adds to the existing literature by studying both the effect of public and non-financial corporations’ debt on economic growth, using a dynamic panel threshold model. While being ambiguous for nonfinancial corporations, the empirical results suggest that public debt has a nonlinear impact on growth and that the accumulation of public debt in the euro area after the financial crisis has been one of the responsible factors for the lethargic growth verified in that monetary union.